2012
DOI: 10.3390/membranes2010016
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli Responsive Ionogels for Sensing Applications—An Overview

Abstract: This overview aims to summarize the existing potential of “Ionogels” as a platform to develop stimuli responsive materials. Ionogels are a class of materials that contain an Ionic Liquid (IL) confined within a polymer matrix. Recently defined as “a solid interconnected network spreading throughout a liquid phase”, the ionogel therefore combines the properties of both its solid and liquid components. ILs are low melting salts that exist as liquids composed entirely of cations and anions at or around 100 °C. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 127 publications
(154 reference statements)
0
69
0
Order By: Relevance
“…The use of ionogel gel-based valves prevents this occurring since ILs have a negligible vapour pressure so that a more robust gel can be obtained. [14] Figure 4 shows the degree of dehydration of the hydrogel and ionogel over time and their linear response (inset). These results demonstrate that valves fabricated using the EMIES ionogel dehydrate about three times slower than those based on the hydrogel.…”
Section: D) Degree Of Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ionogel gel-based valves prevents this occurring since ILs have a negligible vapour pressure so that a more robust gel can be obtained. [14] Figure 4 shows the degree of dehydration of the hydrogel and ionogel over time and their linear response (inset). These results demonstrate that valves fabricated using the EMIES ionogel dehydrate about three times slower than those based on the hydrogel.…”
Section: D) Degree Of Dehydrationmentioning
confidence: 99%
“…Ionic liquids have attracted much attention because of the potential applications in many fields of chemistry and industry due to their chemical and thermal stability, low vapour pressure, high ionic conductivity properties, and tuneable hydrophobic and hydrophilic nature. [14] Incorporating ILs into polymer gels is also attractive as this generates materials with the inherent advantages of ILs within a solid or semi-solid gel-type structure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the achieved progress and the wealth of the literature on the considered topic, a comprehensive review highlighting the various roles of ILs in optical chemical sensors and evaluation of their potential to yield the novel materials for chemical analysis is still needed. To our knowledge, the previous reviews either cover briefly such optical sensors 25,[40][41][42] or focus on the classification and methods of the preparation of the IL-based materials. 25,28,43 Warner et al 44 reported the IL functions while producing photonic IL sensors.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The electrochemical sensing materials prepared using ILs have been discussed in detail in the reviews. [22][23][24][25][26] The ability of some ILs to dissolve a broad range of substances gave rise to studying the possibilities of ILs in optical sensing technologies. ILs can dissolve inorganic gases (O2, CO2, CO, SO2, NO2, H2S, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The employment of ILs as a replacement for water in gel-based polymers has led to the emergence of ionogels as a relatively new subclass of materials. To date, ionogels have been the subject of reviews detailing their preparation and applications in sensor science (95,302). The ionogel template is an ideal matrix as the properties of the IL is hybridized within those of the polymer component, combining the favorable characteristics of both independent phases in one material.…”
Section: Introduction To Ionogelsmentioning
confidence: 99%